2015
DOI: 10.1093/deafed/env042
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Access Among Deaf People: Table 1.

Abstract: Access to health care without barriers is a clearly defined right of people with disabilities as stated by the UN Convention on the Rights of People with Disabilities. The present study reviews literature from 2000 to 2015 on access to health care for deaf people and reveals significant challenges in communication with health providers and gaps in global health knowledge for deaf people including those with even higher risk of marginalization. Examples of approaches to improve access to health care, such as pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
155
0
25

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(202 citation statements)
references
References 82 publications
5
155
0
25
Order By: Relevance
“…Lack of knowledge about Deaf culture is documented in society as well as in healthcare environment [24]. Kuenburg et al also indicated that there are significant challenges in communication among healthcare professionals and Deaf people [25]. Improvement in healthcare access among Deaf people is possible by providing the sign language supported visual communication and implementation of communication technologies for healthcare professionals.…”
Section: Related Workmentioning
confidence: 99%
“…Lack of knowledge about Deaf culture is documented in society as well as in healthcare environment [24]. Kuenburg et al also indicated that there are significant challenges in communication among healthcare professionals and Deaf people [25]. Improvement in healthcare access among Deaf people is possible by providing the sign language supported visual communication and implementation of communication technologies for healthcare professionals.…”
Section: Related Workmentioning
confidence: 99%
“…26 Studies have demonstrated the inaccessibility of health services to Deaf BSL users, [27][28][29][30] including mental health services, resulting in late diagnoses and loss of benefit from early preventative interventions. 31 Poor access to information about health-related matters in BSL results in poor awareness among Deaf community members of mental health issues, including personal support strategies, help-seeking behaviours, routes of referral and treatment options. Often Deaf people use mental health services only when a difficulty has escalated to the point at which secondary/tertiary care intervention is required.…”
Section: Deaf People and Mental Healthmentioning
confidence: 99%
“…It is well evidenced that Deaf people experience significant health inequalities in terms of access to services and health outcomes in a range of domains. 23,31,49,50 In part this results from a failure to adequately provide sign-interpreted access to health care despite the requirements of the Public Sector Equality Duty 5 and the NHS Accessible Information Standard. 51 Lack of cultural competence of health practitioners also plays a part in Deaf people's less than optimum engagement with treatment.…”
Section: Introductionmentioning
confidence: 99%
“…De igual modo, devem ser abordadas as distintas concepções de surdez e de pessoa surda, que incluem suas dimensões fisiológicas, simbólicas e culturais (22). A capacitação em competências culturais para os profissionais de saúde também pode contribuir para favorecer o acesso dos surdos aos serviços (23) . Pautada no projeto clínico-hegemônico-patológico da deficiência, a formação acadêmica desconsidera o tecido social e cultural da surdez (24) .…”
Section: Barreiras Nos Serviços De Saúdeunclassified